Susceptibility to Distraction in Autism Spectrum Disorder: Probing the Integrity of Oscillatory Alpha‐Band Suppression Mechanisms. Issue 4 (27th March 2014) - Murphy, Jeremy W.; Foxe, John J.; Peters, Joanna B.; Molholm, Sophie
<x xml:space="preserve">Abstract</x> When attention is directed to one information stream over another, the brain can be configured in advance to selectively process the relevant stream and suppress potentially distracting inputs. One key mechanism of suppression is through the deployment of anticipatory alpha‐band (∼10 Hz) oscillatory activity, with greater alpha‐band power observed in cortical regions that will ultimately process the distracting stream. Atypical attention has been implicated in autism spectrum disorder (ASD), including greater interference by distracting task‐irrelevant inputs. Here we tested the integrity of these alpha‐band mechanisms in ASD using an intersensory attention task. Electroencephalography (EEG) was recorded while participants were cued on a trial‐by‐trial basis to selectively deploy attention to the visual or auditory modality in anticipation of a target within the cued modality. Whereas typically developing (TD) children showed the predicted alpha‐band modulation, with increased alpha‐band power over parieto‐occipital scalp when attention was deployed to the auditory compared with the visual modality, this differential pattern was entirely absent at the group level in the ASD cohort. Further, only the ASD group showed impaired performance due to the presence of task‐irrelevant sensory information. These data suggest that impaired modulation of alpha‐band activity plays a role in increased distraction from extraneous sensory inputs in ASD. Autism Res2014, 7: 442–458. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.